Patients' perspectives on the use of the Montgomery-Asberg depression rating scale self-assessment version in primary care. (1st October 2016) - Wikberg, Carl; Pettersson, Agneta; Westman, Jeanette; Björkelund, Cecilia; Petersson, Eva-Lisa
Abstract: Objective: The aim of the current study was to better understand how patients with depression perceive the use of MADRS-S in primary care consultations with GPs. Design: Qualitative study. Focus group discussion and analysis through Systematic Text Condensation. Setting : Primary Health Care, Region Västra Götaland, Sweden. Subjects: Nine patients with mild/moderate depression who participated in a RCT evaluating the effects of regular use of the Montgomery-Åsberg Depression Self-assessment scale (MADRS-S) during the GP consultations. Main Outcome measure: Patients' experiences and perceptions of the use of MADRS-S in primary care. Results: Three categories emerged from the analysis: (I) confirmation; MADRS-S shows that I have depression and how serious it is, (II) centeredness; the most important thing is for the GP to listen to and take me seriously and (III) clarification; MADRS-S helps me understand why I need treatment for depression. Conclusion : Use of MADRS-S was perceived as a confirmation for the patients that they had depression and how serious it was. MADRS-S showed the patients something black on white that describes and confirms the diagnosis. The informants emphasized the importance of patient-centeredness; of being listened to and to be taken seriously during the consultation. Use of self-assessment scales such as MADRS-S could find its place, but needs to adjust to the multifaceted environment that primary care provides. Key Points: Patients with depression in primary care perceive that the use of a self-assessment scale in the consultation purposefully can contribute in several ways. The scale contributes to Confirmation: MADRS-S shows that I have depression and how serious it is. Centeredness: The most important thing is for the GP to listen to and take me seriously. Clarification: MADRS-S helps me understand why I need treatment for depression.